Analysis of Production Trends as an Effort to Generate Business Income in the MSME Printing Sector: A Case Study of CV Rijiki Advertising, Tolitoli.: Analisis Tren Produksi sebagai Upaya Menghasilkan Pendapatan Usaha di Sektor Percetakan UMKM: Studi Kasus CV Rijiki Advertising, Tolitoli. - Ismail Ismail; Bustari Bustari; Edi Yanto; Riska Riska (International Journal of Economic Entrepreneurship and Business Management, 2024)
The purpose of this study is to analyze the trend of production volume of the printing sub-sector of small and medium enterprises using a case study of CV Rijiki Advertising in Tolitoli Regency. As part of the creative economy, the printing industry is essential in supporting various local economic activities, including promotional activities from other small and medium enterprises, government agencies, and educational institutions. This study is quantitative descriptive using trend analysis of CV Rijiki Advertising Tolitoli's production volume data for 2021 to 2023. The results show that there is a trend of moderate production volume increasing since 2021 in line with economic recovery and increased spending on promotional advertising by institutional clients. The production volume of the billboard printing business in 2021 was 805 units, in 2022 it was 839 units and in 2023 it was 875 units. The production volume of data boards in 2021 was 420 units, in 2022 it was 632 units, and in 2023 it was 683 units. The production volume of data boards in 2021 was 72 units, in 2022 it was 93 units and in 2023 it was 110 units. This increase reflects an average growth of around 20.93% per year, which indicates that there is a post-pandemic economic recovery and market demand for outdoor promotional media is still increasing. Actionable recommendations are provided regarding strategies on how to strengthen business sustainability in the face of market dynamics and technological challenges.